2021
DOI: 10.7759/cureus.16856
|View full text |Cite
|
Sign up to set email alerts
|

Time to Improvement After Corticosteroid Injection for Trigger Finger

Abstract: Purpose Trigger finger is a commonly occurring hand condition that presents with symptoms of pain, clicking, locking, and catching of the finger. A common non-operative management option is corticosteroid injection. The purpose of this study was to evaluate the short-term patient response to corticosteroid injections for trigger finger. Methods The patients of six fellowship-trained orthopedic hand surgeons who underwent a corticosteroid injection for trigger finger between Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…This might be a coincidence, and a long-term followup of the participants might show if this is a true The sequence of relief of symptoms was similar after both injection techniques: pain seems to subside first, followed by improvement of stiffness while triggering seems to linger (Figure 3). These results are consistent with the findings by Seigerman et al (2021), but the timing of symptom relief differed. While they found that 82% had complete improvement in pain and 65% triggering at 3 weeks, our corresponding results were 78% and 45%, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This might be a coincidence, and a long-term followup of the participants might show if this is a true The sequence of relief of symptoms was similar after both injection techniques: pain seems to subside first, followed by improvement of stiffness while triggering seems to linger (Figure 3). These results are consistent with the findings by Seigerman et al (2021), but the timing of symptom relief differed. While they found that 82% had complete improvement in pain and 65% triggering at 3 weeks, our corresponding results were 78% and 45%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, there are few studies that focus on the time aspect of symptom relief after this treatment. One study showed that triggering was resolved in 79% of the patients within a month and that the mean number of days to resolution of trigger phenomenon was 8.8 (Yak et al., 2020); another found that most patients experience relief of pain and triggering by 3 weeks after injection, with triggering lagging behind pain relief (Seigerman et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Many patients, when given the option of cortisone injection, want to know how soon they might see improvement. Seigerman et al [ 33 ] investigated time to improvement after cortisone injection in a study involving 452 patients and found that most patients experience relief of pain and triggering at 3 wk following cortisone injection[ 33 ]. They reported that the majority of patients had some pain relief within the first week after cortisone injection.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment can either involve surgery to cut pulley or local corticosteroid injection. Corticosteroid injection shows a significant improvement in patient's symptoms, so it is recommended in most of the patients suffering this condition [11].…”
Section: Trigger Fingermentioning
confidence: 99%
“…In this treatment, there are no such side effects as the systemic use, and on the other hand the medicine can act on the problematic area, like injecting the injectable form of triamcinolone in the joint space. Usually to eliminate patient's pain in this treatment, corticosteroid is mixed with local anesthetic agents like lidocaine and is injected directly in the joint space either landmark-guided or sonographicguided [3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%